STRATEGI PEMASARAN PAKET UMROH DI PAKEM TOURS PEKANBARU - Nordiana Gustina; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Currently the competition in tourism industry is getting tighter. One of the tour and travel companies which is named Pakem ToursPekanbaru also faces an intense competition in Pekanbaru with various competitors bith online company and fellow tour and travel company. Therefore, this study aims to describe the marketing strategy (Segmenting, Targeting and Positioning) in Pakem ToursPekanbaru. The research’s data was collected through interviews with the management including employees. The result of research shows thatPakem ToursPekanbaru is using segmentation base such as geografic segmentation, demografic segmentation, psikografic segmentation. In terms of targeting, Pakem ToursPekanbaru uses determination different target market and focus on umrah and haji product. In terms of posiyioning, Pakem ToursPekanbaru uses base price, quality and competitor, the company also do the steps in determination of market position. Keywords: Segmentation, Targeting, Positioning, Tour and Travel